2011
DOI: 10.1016/j.biomaterials.2011.08.065
|View full text |Cite
|
Sign up to set email alerts
|

The promotion of neurite sprouting and outgrowth of mouse hippocampal cells in culture by graphene substrates

Abstract: a b s t r a c tGraphene has been demonstrated in many biomedical applications and its potentials for neural interfacing. Emerging concerns on graphene, as a biomedical material, are its biocompatibility and how biologically targeted tissue/cells respond to it. Relatively few studies attempted to address the interactions of graphene or its derivatives with the tissues/cells, while very few reports on neural system. In this study, we tried to explore how neurites, one of the key structures for neural functions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
300
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 389 publications
(319 citation statements)
references
References 39 publications
17
300
0
2
Order By: Relevance
“…Li et al (2011) observed that graphene films exhibit excellent biocompatibility in primary cultured rat hippocampal neurons and are also capable of promoting growth and sprouting of neurons, especially during the early development phase.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2011) observed that graphene films exhibit excellent biocompatibility in primary cultured rat hippocampal neurons and are also capable of promoting growth and sprouting of neurons, especially during the early development phase.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple recent studies have focused on the use of graphene and graphene composites in biomedical applications. 133,[228][229][230][231] From these studies, as well as other cytotoxicity studies on graphene and related compounds, 69,232-251 we are able to draw some conclusions regarding graphene's biological toxicity.…”
Section: Environmental and Biological Toxicity Of Graphenementioning
confidence: 90%
“…Li et al showed that mice hippocampal neurons could be grown on CVD graphene, with the scaffold even promoting neutrite growth. 230 Additional studies have shown that graphene can also be used as a scaffold for human colorectal adenocarcinoma HT-29 cells 251 and human stem cells. 229,231 Mammalian in vivo studies of the toxicity of graphene compounds have been conducted in mice.…”
Section: Environmental and Biological Toxicity Of Graphenementioning
confidence: 99%
“…The results revealed that graphene substrates exhibited excellent biocompatibility, as cell viability and morphology were not affected in comparison with the control specimen. In addition, neurite numbers and average neurite length on graphene were significantly enhanced during 2-7 days after cell seeding compared to tissue culture polystyrene (TCP) substrates [105] .…”
Section: Bio-interface Of Carbon Nanotube and Graphene Based Materialmentioning
confidence: 99%